PENGARUH UKURAN PERUSAHAN, LEVERAGE, PROFITABILITAS, DAN CAPITAL INTENSITY TERHADAP TARIF PAJAK EFEKTIF WAJIB PAJAK BADAN - Kurnia Krisna Hari (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2023)
The purpose of this research is to see the effect of company size, leverage, profitability, and capital intensity on the effective tax rate for corporate taxpayers. This study uses banking financial report data listed on the Indonesia Stock Exchange. The total population is 43 banks, while the research sample is 14 banks with a total period of 4 years for each bank. The type of research used is associative and the analysis technique used is the classical assumption test and multiple linear regression using the Statistical Program for Social Science. The results of the study found that company size, leverage, profitability, and capital intensity have an effect on the effective tax rate simultaneously. Partially, firm size and leverage have no effect on the effective tax rate, while profitability and capital intensity have an effect on the effective tax rate.